Pengaruh penggunaan saponin dan serbuk bijik pinang terhadap mortalitas keong mas (Pomacea canaliculata L.) dan keamanan ikan lele - Faisal, Sayed; Husni, Husni; Sapdi, Sapdi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala)
This study aims to determine the effect of the application of saponin and betel nut powder on mortality snails and safety of aquatic biota. The design used in this study is a non-factorial completely randomized design that Consist 10 treatments with 3 replications, so there are 30 experimental units. Variables measured included: 1). The percentage rate of consumption of snails, 2). Mortality of snails, 3). Time of death snails, 4). Mortality catfish, Â 5). Time of death catfish. Based on the observations of all variables that include the percentage rate of consumption of snails, snails mortality, time of death snails, catfish mortality, time of death catfish can be said that the use of saponins and betel nut powder at the lowest dose has caused mortality of snails up to 100%. While the use of saponin with doses â¥ 0.375 g tub-1 will result in the death of catfish â¥ 47.67%, while the application of betel nut powder with doses â¥ 6 g tub-1 will result in the death of catfish â¥ 43.33%. Lower its high mortality rate affecting the percentage of consumption, the average percentage of time of death.